Production and antibacterial properties of flavour and flavonoid compounds from cultured tissues of citrus hystrix D. C. ('Limau Purut') - Roowi, Suri (2001)
Analyses of the flavour compounds from the selected parts of flower, seedlings grown in-vitro and callus cultures of Citrus hystrix D.C. were performed using the gas chromatography (GC) technique. The results showed that the major flavour compound obtained from the flower was citronellal. Young seedlings g rown in-vitro on the Murashige and Skoog (MS) basal medium without plant growth regulators did not produce an citronellal. Nevertheless, the quantity of limonene was remarkably higher (101.00 ± 5.24 119/g fwt. tissue) than in the petal and ovary and pollen plus anther. Callus derived from stem treated with 2.0 mg/l (w/v) NAA plus 1 .0 mg/l (w/v) kinetin reached a maximum growth (0.94 ± 0.08 g fwt.lculture) after six weeks of culture. No callus was fou nd from the leaf and peel. Maximum production of flavour compou nds Le. cyclohexanol, limonene and p-pinene were obtained after three and four weeks of culture. Treatment of the C. hystrix stem-derived callus with 1.0 mg/l (w/v) of kinetin showed higher growth (0.42 ± 0.04 g fwt/culture) than all treatment with NAA. Most of the flavour compounds in the callus were found highest after being treated with 5.0 mgll (w/v) of NAA. Addition of various concentrations of salicylic acid (0 to 20.0 mM), yeast extract (0 to 0.5%) and alginate (0 to 0.5%) into the medium, decreased the callus g rowth. However, treatment of stem-derived callus with 0.3% of (w/v) of alginate resulted in higher growth (0.88 ± 0.05 g fwt/culture) than the other treatments. On the other hand, callus treated with yeast extract and salicylic acid were able to syntheses two and six additional compounds respectively compared to the control. Treatment of C. hystrix stem-derived callus with proline and phenylalanine decreased the callus growth but Significantly increased the production of flavour compounds i.e. p-cymene, terpineol, citronellal , citronellol , y-terpene and β-pinene. Analyses of flavonoid compounds from young seedlings, callus and different parts of C. hystrix intact plant such as leaf, flower, stem and fruit was performed by high performance liquid chromatography technique (HPLC). The highest production of flavonoids i.e. naringin (11.66 ± 0.76 mg/g dwt. tissue), rutin (34.63 ± 1.69 mg/g dwt. tissue) and kaempferol (3.01 ± 0.02 mg/g dwt. tissue) was found in the peel; hesperidin (3.21 ± 0.23 mg/g dwt. tissue) in the leaf and quercetin (0.68 ± 0.04 mg/g dwt. tissue) in the whole flower. In the young seedlings, naringin (5.26 ± 0.25 mg/g dwt. tissue), and rutin (0.91 ± 0.03 mg/g dwt. tissue) were found in high concentration in the stem compared to the leaf and root. The naringin and rutin content of stem-derived callus showed the maximum values at 2.29 ±. 0.09 and 0.90 ±. 0.03 mg/g dwt. tissue respectively after six weeks of culture. Treatment of stem-derived callus with 0.3% and 0.5% (w/v) of agarose gave the highest production of naringin and rutin at 12.13 ± 0.07 and 3.09 ± 0.05 mg/g dwt. tissue, respectively. Addition of 2.0 mM phenylalanine into the culture medium also increased the production of naringin (24.05 ±. 1.02 mg/g dwt. tissue) and rutin (3.52 ± 0.12 mg/g dwt. tissue). The essential oils (contains flavour compounds) and the methanolic extracts (contains flavonoid compounds) were obtained from peel, leaf, juice and stem-derived callus. Results showed that most extracts were able to inhibit gram positive and gram negative bacterial growth.